Integration of high‐risk human papillomavirus into cellular cancer‐related genes in head and neck cancer cell lines. Issue 5 (25th February 2017) - Walline, Heather M.; Goudsmit, Christine M.; McHugh, Jonathan B.; Tang, Alice L.; Owen, John H.; Teh, Bin T.; McKean, Erin; Glover, Thomas W.; Graham, Martin P.; Prince, Mark E.; Chepeha, Douglas B.; Chinn, Steven B.; et al.
ABSTRACT: Background: Human papillomavirus (HPV)‐positive oropharyngeal cancer is generally associated with excellent response to therapy, but some HPV‐positive tumors progress despite aggressive therapy. The purpose of this study was to evaluate viral oncogene expression and viral integration sites in HPV16‐ and HPV18‐positive squamous cell carcinoma lines. Methods: E6/E7 alternate transcripts were assessed by reverse transcriptase‐polymerase chain reaction (RT‐PCR). Detection of integrated papillomavirus sequences (DIPS‐PCR) and sequencing identified viral insertion sites and affected host genes. Cellular gene expression was assessed across viral integration sites. Results: All HPV‐positive cell lines expressed alternate HPVE6/E7 splicing indicative of active viral oncogenesis. HPV integration occurred within cancer‐related genes TP63, DCC, JAK1, TERT, ATR, ETV6, PGR, PTPRN2, and TMEM237 in 8 head and neck squamous cell carcinoma (HNSCC) lines but UM‐SCC‐105 and UM‐GCC‐1 had only intergenic integration. Conclusion: HPV integration into cancer‐related genes occurred in 7 of 9 HPV‐positive cell lines and of these 6 were from tumors that progressed. HPV integration into cancer‐related genes may be a secondary carcinogenic driver in HPV‐driven tumors. © 2017 Wiley Periodicals, Inc. Head Neck 39: 840–852, 2017